Antioxidant activity and in vitro inhibition of tumor cell growth by leaf extracts from the carob tree (Ceratonia siliqua) - Custódio, Luísa (2015)
The methanol leaf extracts of female cultivars of the carob tree [Ceratonia siliqua L. (Fabaceae)] and of hermaphrodite and male trees were investigated for their contents of phenolic compounds, their in vitro antioxidant activity, measured by 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical-scavenging and linoleic acid system assays, and their in vitro tumor growth inhibition on HeLa cells. The different cultivars and trees showed high levels of phenols, and considerable variations in the amount of these compounds. The extracts showed significant radical scavenging activity (RSA), which was not significantly affected by the gender of the tree. From the female cultivars tested, Galhosa exhibited the highest RSA. Gender significantly affected the antioxidant activity of the extracts measured by the linoleic acid system assay, and males and hermaphrodites showed the highest activities. The extracts displayed a remarkable ability to inhibit tumor cell proliferation, and their bioactivity varied with different cultivars or trees tested. Extracts from male and hermaphrodite trees exhibited higher capacity to inhibit the proliferation of HeLa cells than the female cultivars.